The Need For Educational Psychology In The Industrial Era 4.0 Entering A Society 5.0 - Manurung, Mikha Marsaulina Cecyana; Slameto (International Conference on Elementary Education, 2024)
Industrial Revolution 4.0 and Society 5.0 is a phenomenon that describes the progress and development of industry and society which is characterized by the appearance of technology. Revolutions that occur in the world, both the Industrial Revolution 4.0 and Society 5.0, provide many changes in various fields, one of which is education. However, technology can provide many benefits to improve the quality of education if used properly. The research method used in making this scientific paper is qualitative with literature review from various journals and books. The results obtained are the role of Educational Psychology in facing the era of the Industrial Revolution 4.0 and Society 5.0, namely, to form good student character, direct the use of technology as a means of self-development, and to deal with changes in the conventional teaching and learning process to become more modern in order to improve the skills of using technology and the quality of human resources. Efforts that can be implemented to improve skills, efficiency, effectiveness, and wisdom in using technology are through Digital Literacy, Distance Learning, Blended Learning, and honing students' Higher Level Thinking Skills (HOTS).